Photofabrication of Micro-Scale Scaffolds for Cell Alignment and Orientation - FUJITA, Akiko; FUJITA, Katsumasa; MATSUDA, Takehisa; NAKAMURA, Osamu (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
In a living body, cells are organized in complex three-dimensional arrangements where individual cells cooperate to perform the functions required of organs. In order to artificially reproduce the cell morphology of a living body, technology is required to control cell adhesion and extension, as well as alignment and orientation. Here, we propose and demonstrate the use of a photofabrication technique to produce unique structures that can be used as cell growth substrates. Photocurable gelatin, consisting of styrene-derivative gelatin and comphaquinone (a photoinitiator), was used to create the biocompatible structures. Near-infrared laser irradiation was focused on the gelatin and two-photon absorption occurred at the focus, inducing spatially localized polymerization and solidification of the gelatin structure with high resolution. The photofabrication technique also allows the production of three-dimensional cell scaffolding. Due to the localization of polymerization combined with scanning the position of the laser focus, it is possible to create arbitrary three-dimensional gelatin structures. After photo-induced solidification, non-solidified parts of the gelatin (i. e. the non-irradiated regions) were washed out by rinsing with deionized water. In the experiments described here, a mode-locked Ti: sapphire laser (780nm, 82MHz, 80fs) was used as the irradiation source, and a grid-like structure of micron-order resolution was fabricated by scanning the laser beam and exposing regions of gelatin on a cover glass. Rat cardiomyocytes were then cultured on the fabricated structure. Seventy percent of the cardiomyocytes on the gelatin structure showed cell extension parallel to the structure, and cell extension was observed to occur predominantly along the edges of the gelatin regions. In contrast, cardiomyocytes cultured on dishes without any structure showed disordered extension and did not align parallel to each other.